Tourist Diners’ Demographic Characteristics and Neophobic Tendencies to Local Cuisine in Botswana - Delly Mahachi Chatibura (International Journal of Gastronomy Research)
An attempt to explore the influence of demographic characteristics on the food neophobic tendencies of diners is undertaken. Using independent sample t tests and analysis of variance, the influence of age, gender, nationality and the level of education, on the perceived avoidance of traditional Setswana cuisine consumption was investigated. Two hundred and forty nine diners from 47 restaurant facilities in Gaborone formed the sample. Key findings from the study reveal that, on average, (though statistically insignificant), male respondents experienced higher levels of Setswana cuisine neophobia than female diners. Furthermore, the paper noted that diners above 50 years of age reported significantly higher levels of neophobia than lower age groups. The findings also indicate to some extent that diners may not necessarily be compelled to taste local cuisine based on familiarity. The paper concludes by suggesting the need for more research on the relationship between familiarity and shared cultural contexts, with food neophobia.